Discussion of Trials of Legal Disputes Involving Independent Auditors: Some Empirical Evidence - Ettredge, Michael L. (Journal of Accounting Research, 1991)
Michael L. Ettredge, Discussion of Trials of Legal Disputes Involving Independent Auditors: Some Empirical Evidence, Journal of Accounting Research, Vol. 29, Studies on Accounting Institutions in Markets and Organizations (1991), pp. 186-193